PTEN Plays Dual Roles As a Tumor Suppressor in Osteosarcoma Cells. Issue 9 (25th April 2017) - Xi, Yongming; Chen, Yan
ABSTRACT: Osteosarcoma (OS) is the most common primary bone cancer, which occurs primarily in children and adolescents. Functional loss of the tumor suppressor PTEN has been demonstrated in bone malignancies including OS. We have recently reported that Pten expression inversely correlates with OS aggressiveness in mouse models. However, the mechanism whereby PTEN exerts its anti‐tumor effect remains unknown. In this study, we first examined the expression of PTEN in human OS cell lines including U2OS, MG63 and Saos‐2, and found that PTEN expression is reduced as compared to normal human osteoblasts. The downregulation of PTEN also associates with activation of AKT pathway. We then treated previously reported mouse OS tumor cells MOTO‐ Rank Δ/ΔOC and human OS cell line U2OS with PTEN inhibitor VO‐OHpic to investigate how PTEN impacts tumor cell behaviors. Our results showed that PTEN inhibits tumor cell proliferation, migration and invasion, but enhances tumor cell apoptosis. However, PTEN has no effects on tumor cell senescence and chemotaxis. PTEN also fails to induce tumor cells differentiation toward osteoblast lineage. On the other hand, PTEN inhibits tumor associated osteoclast differentiation. Moreover, overexpression of PTEN using gene transfer in U2OS cells inhibits proliferation but increases apoptosis. These findings indicate that PTEN not only targets tumor cells themselves by impacting cell behaviors, but also blocks osteoclast‐mediated bone destruction, leading to interruption of the vicious cycle during osteosarcomagenesis. Loss of PTEN may consequently facilitate tumor growth and expansion in bone. Restoration of fully functional PTEN using gene therapy represents a potential approach against OS. J. Cell. Biochem. 118: 2684–2692, 2017. © 2017 Wiley Periodicals, Inc. Abstract : Tumor suppressor PTEN may play dual anti‐tumor roles, targeting not only tumor cell behaviors (e.g., proliferation, migration, invasion, and apoptosis), but also osteoclast differentiation, leading to the interruption of the "vicious cycle" during osteosarcomagenesis. Restoration of functional PTEN represents a potential strategy against osteosarcoma.